Astroglial IFITM3 mediates neuronal impairments following neonatal immune challenge in mice. Issue 5 (4th February 2013) - Ibi, Daisuke; Nagai, Taku; Nakajima, Akira; Mizoguchi, Hiroyuki; Kawase, Takahiro; Tsuboi, Daisuke; Kano, Shin‐Ichi; Sato, Yoshiaki; Hayakawa, Masahiro; Lange, Ulrike C.; Adams, David J.; Surani, M. Azim; et al.
Abstract : Interferon‐induced transmembrane protein 3 (IFITM3) ıplays a crucial role in the antiviral responses of Type I interferons (IFNs). The role of IFITM3 in the central nervous system (CNS) is, however, largely unknown, despite the fact that its expression is increased in the brains of patients with neurologic and neuropsychiatric diseases. Here, we show the role of IFITM3 in long‐lasting neuronal impairments in mice following polyriboinosinic‐polyribocytidylic acid (polyI:C, a synthetic double‐stranded RNA)‐induced immune challenge during the early stages of development. We found that the induction of IFITM3 expression in the brain of mice treated with polyI:C was observed only in astrocytes. Cultured astrocytes were activated by polyI:C treatment, leading to an increase in the mRNA levels of inflammatory cytokines as well as Ifitm3 . When cultured neurons were treated with the conditioned medium of polyI:C‐treated astrocytes (polyI:C‐ACM), neurite development was impaired. These polyI:C‐ACM‐induced neurodevelopmental abnormalities were alleviated by ifitm3 −/− astrocyte‐conditioned medium. Furthermore, decreases of MAP2 expression, spine density, and dendrite complexity in the frontal cortex as well as memory impairment were evident in polyI:C‐treated wild‐type mice, but such neuronal impairments were not observed in ifitm3 − / − mice. We also found that IFITM3 proteins were localized to the early endosomes of astrocytes following polyI:C treatment and reduced endocytic activity. These findings suggest that the induction of IFITM3 expression in astrocytes by the activation of the innate immune system during the early stages of development has non‐cell autonomous effects that affect subsequent neurodevelopment, leading to neuropathological impairments and brain dysfunction, by impairing endocytosis in astrocytes. GLIA 2013